Histopathological changes in ovaries of zebrafish (danio rerio) following administration of deltamethrin - (:unkn) unknown (My University, 2009)
The aim of this study is to investigate histopathological changes of different doses of deltamethrin in zebrafish (Danio rerio) ovaries. The pyrethroid class of insecticides, including deltamethrin, is being used to substitute organo-chlorines and organophosphates in pest-control programs because of low environmental persistence and toxicity. It has a high safety factor, rapidly metabolizes and is known to enter into fish-body via gills. It is highly toxic to fish and other aquatic organisms. The zebrafish are divided into three groups (n=30) according to their different deltamethrin (group I: 0.5 u.g/L deltamethrin; group II: 1 ug/L deltamethrin; group III: control group) doses. Morphological changes of ovarium were investigated by light microscopy with different fixatives (10% neutral buffered formalin & Bouin's) and stains (hematoxyline-eosin, toluidine blue, best carmine, PAS method). An increase in atretic oocytes was observed, and oocytes were depraved and grew unhealthily, in this study. The number of oosites in the ovarium of the study groups was less to that of control group where these changes were not observed. This study shows that deltamethrin has significant negative effects on oogenesis in zebrafish. In summary, our study revealed that acute doses of deltamethrin slowed down oogenesis in the fish.
Keywords: Deltamethrin; Histopathology; Ovary; Zebrafish